Germination of Sardinian black and white Vitis vinifera seeds according to treatments and dormancy factors - Orrù, Martino; Santo, Andrea; Ucchesu, Mariano; Sarigu, Marco; d’hallewin, Guy; Sau, Silvia; Bacchetta, Gianluigi (Revista Ciência Agronômica, 2023)
Physiological dormancy of Vitis vinifera seeds jeopardises breeding programs and biodiversity evolution. To increase the knowledge on dormancy breaking, seeds of white and black Sardinian grape cultivars (cvs) were exposed to different pre-germination treatments. To shed light on the physiological and structural factors involved in seed dormancy, the contents of oil, abscisic acid, gibberellic acid, 3-indolacetic acid, condensed tannins, and total polyphenols were determined. In addition, sectioned seeds were observed by SEM to determine the morphological and anatomical characteristics. Dormancy break in white, but not in black grape seeds, occurred under almost all imposed pre-germination treatments. Among red cvs, only seeds from ‘Cagnulari’ germinated when kept at 25 °C. Chilling seeds of the white cvs ‘Malvasia sarda’ and ‘Vernaccia di Oristano’ for 30 d resulted in the most effective treatment. Compared to white cvs, seeds of red ones owned 7 times higher levels of abscisic acid however, gibberellic acid content resulted 4 times less. Concerning the coat characteristics, red cv seeds had a thicker cuticle (6–10 µm) than white (4–6 µm) ones, however the most significant diversities were found for the inner integument, where in addition to size variances, palisade cell wall were structurally different.